2020
DOI: 10.1002/adfm.201906205
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐Factor Free Multicomponent Nanocomposite Hydrogels That Stimulate Bone Formation

Abstract: Synthetic osteo‐promoting materials that are able to stimulate and accelerate bone formation without the addition of exogenous cells or growth factors represent a major opportunity for an aging world population. A co‐assembling system that integrates hyaluronic acid tyramine (HA‐Tyr), bioactive peptide amphiphiles (GHK‐Cu2+), and Laponite (Lap) to engineer hydrogels with physical, mechanical, and biomolecular signals that can be tuned to enhance bone regeneration is reported. The central design element of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 70 publications
2
53
0
Order By: Relevance
“…The chosen peptide sequence contributed to high water retention and stimulated the formation of blood vessels. Moreover, the gel was injectable, which avoids any extensive surgery [ 220 ].…”
Section: In Vivo Outcomes and Clinical Trialsmentioning
confidence: 99%
“…The chosen peptide sequence contributed to high water retention and stimulated the formation of blood vessels. Moreover, the gel was injectable, which avoids any extensive surgery [ 220 ].…”
Section: In Vivo Outcomes and Clinical Trialsmentioning
confidence: 99%
“…Paper effect of LAPONITE® on osteogenic differentiation of skeletal populations has been widely reported [1][2][3][31][32][33][34][35][36] and observed both when applied as a dispersed additive to cell culture media 2,3,31,32 and as a composite in polymeric biomaterials. 5,[33][34][35][36] In discussions of potential mechanisms in the literature it is frequently suggested that nanoclay bioactivity could be attributed to LAPONITE® degradation products. [2][3][4][5][6][7][8]31 Lithium is of particular interest in this context for its well-established pharmacological action as an agonist of the canonical Wnt pathway.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…LAPONITE® nanoparticle addition caused a pronounced enhancement in ALP activity, calcium deposition and ALPL and COL1A1 gene expression in agreement with previous studies. [1][2][3]5,[31][32][33][34][35][36] Interestingly, genes for the principle osteogenic transcription factors, Runx2 and Osterix (SP7), were not upregulated in response to LAPONITE®, suggesting alternative signaling pathways lie behind the phenotypic changes observed. This observation is in contrast with some previous studies which describe upregulation of Runx2 with LAPONITE® addition, 2,3,32 although, notably, a whole transcriptome analysis of LAPONITE® effects on HBMSCs also recorded neither gene as being differentially expressed under similar conditions (RUNX2, false-discovery rate-adjusted P = 0.519 as calculated by authors from source dataset; SP7, undetermined).…”
Section: Papermentioning
confidence: 99%
“…11 Peptide derivatives are also relevant when considering biomineralization at interfaces. 12,13 Peptides can form hybrids with relevant nanostructures based on carbon for subsequent self-assembly into intriguing materials. 14,15 The structural features of proteins and peptide fragments are undoubtedly the focus of a large body of research.…”
Section: Introductionmentioning
confidence: 99%